Trade, its history and its influence on civilization - Trumbull, James Dunbar (My University, 1896)
Introduction: The history of trade is the history of civilization and perhaps there is no one factor in the progress of the world that has contributed more to the growth and culture of humanity than trade. At first this may seem a broad statement but when one considers the various ways in which this factor has aided in the progress of the world one cannot doubt the above statement.
Citation: Trumbull, James Dunbar. Trade, its history and its influence on civilization. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: History; Trade; Civilization; Culture; Humanity; Theses; Manuscripts (documents)